The effects of displaying availability sections of an automated driving function - Danner, Simon; Feierle, Alexander; Gary, Sebastian; Bengler, Klaus (Frontiers in Future Transportation, 2023)
So far, there has been little research into displaying the availability of a higher-level automated driving system. The benefits of presenting availability times while driving automatically have already been discussed, but there are no findings on giving information on all availability sections (operational design domains) independent of the current state of the automated driving system. This work aims to close this gap by conducting a driving simulator study with N = 54 participants to verify whether an overview display of all the road sections on which automated driving is possible has a positive effect on the participants’ acceptance, usability, workload, and task performances. Results showed that the presentation of this additional information had a significantly positive influence on both acceptance and task performance. The outcomes of this work indicate that the required transparency-creating information of the automated driving system should not be limited to safety-related information or the phases of automated driving itself.